Relasi Persepsi Visualisasi Desain Kemasan Obat Sakit Kepala Terhadap Kepercayaan Konsumen - Miranti Nurul Huda (CandraRupa : Journal of Art, Design, and Media, 2019)
The interaction between consumer and product packaging design is a process of meaning which is involves vision and thought processes that influenced by knowledge, references, experience, and cultural backgrounds. Packaging products have an important role as dealing directly with prospective buyers and consumers and become the first experience with the product. Especially packaging for drugs, that are not only to attract consumers but also must meet safety standards for consumers to consume the drug. The purpose of this study to discover the facts of how consumers perceive packaging design and its influence on purchasing decisions and verify the trust level of the product. This research will use quantitative methods with semantic approach and using questionnaire to collecting data. Questions in the questionnaire using two scales measuring, Likert scale to measure respondent’s psychometric factors. The expected outcome of this research is the acquisition of a formulation headache medicine packaging design that maximizes consumer confidence in the usefulness of the drug without prejudice to the safety of consumers when consumed.